Materiais análogos à dentina: comparação com dentina humana no comportamento adesivo e mecânico - Dalla Nora, Fernanda (2023)
The present study is divided into three studies where the adhesive and mechanical behavior of an glass fiber-reinforced epoxy resin (GFRER) was evaluated compared to human dentin. Article 1 investigated the effect of presenting commercially available (plate and round-rod) and experimental GFRER material compared to dentin in a microshear bond strength (μSBS) (wire-loop) test. Specimens were fabricated (Ø 10 mm × 3 mm thick), prepared (N=13) and aged (12,000 × 5 ͦ C - 55 ͦ C). Surface roughness, contact angle, elastic modulus, sorption and solubility, failure and topographic analysis were performed. Statistical analysis showed that μSBS results were statistically influenced by the substrate used (p < 0.001). There was no statistical difference in bond strength between dentin (8.40 MPa) and dowel (10.24 MPa) (p= 0.466). Dentin and round-rod had the same number of pretest failures, while the experimental group had the highest number of pretest failures. Sorption and solubility analyzes showed that the materials had no effect of dimensional changes in volume and weight on liquid sorption or material solubility. Article 2 compared the resistance μSBS (wire-loop) of dentin with GFRER material (round-rod) submitted to different surface treatments: CTR- no treatment, HF5%, HF10%, H3PO437% and SAND- blasting with aluminum oxide particles (110 μm). Specimens were fabricated (Ø 10 mm × 3 mm thick), prepared (N=13) and aged (12,000 × 5 ͦ C - 55 ͦ C). Surface roughness, contact angle, failure and topographic analysis were performed. The μSBS bond strength results were statistically influenced by the surface treatment of the substrate used. Only the H3PO4 group showed bond strength, roughness and contact angle statistically similar to dentin. Failure analysis showed that most adhesive failures between groups except SAND. Topographic analysis showed that all proposed surface treatments modified the substrate surface when compared to the control group. Article 3 aimed to compare the resistance to fatigue of dentin with the GFRER material (round-rod) (Ø=10 mm, thickness =2.0 mm) subjected to different surface treatments (same article 2), cemented to glass ceramic (Ø=10 mm, thickness=1.5 mm). All specimens were aged through 25,000 thermal cycles and stored for 6 months. Roughness, contact angle, topographic and fractographic analyzes were performed. The DENT group showed the lowest values of load to failure and number of cycles to failure in fatigue (637.33 N), not showing statistical similarity with any of the groups tested (p > 0.05). The topography showed that all proposed surface treatments modified the surface when compared to the CTR group. All fractographic inspections demonstrated failure as a radial crack. The use of the GFRER material should be used with caution as an analogue to dentin, as it is not capable of mimicking all the properties of human dentin in in vitro studies.